2008
DOI: 10.1007/s10459-007-9097-8
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for overcoming problems in teaching interviewing skills to medical students

Abstract: The objective of this paper is to draw attention to four features that distinguish the pedagogy of patient interviewing from the teaching of other clinical skills: (a) students are not naïve to the skill to be learned, (b) they encounter role models with a wide variability in interviewing styles, (c) clinical teachers are not usually specialists in the behavioral sciences, including patient interviewing, and (d) the validity of the methods used for assessment of interviewing skills is uncertain. We propose to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Moreover, aspects of personality such as conscientiousness, extraversion, and openness which influenced academic achievement in our study could be used to gain more insight into the profile of the student who plans to enroll. This is in line with the belief that in the selection process, secondary school GPA alone is insufficient for predicting academic achievement (Benbassat & Baumal, 2007). These indicators could be used in university admission policies or for mapping students' (knowledge) level from, or even before, the time students start their university education.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, aspects of personality such as conscientiousness, extraversion, and openness which influenced academic achievement in our study could be used to gain more insight into the profile of the student who plans to enroll. This is in line with the belief that in the selection process, secondary school GPA alone is insufficient for predicting academic achievement (Benbassat & Baumal, 2007). These indicators could be used in university admission policies or for mapping students' (knowledge) level from, or even before, the time students start their university education.…”
Section: Discussionsupporting
confidence: 71%
“…In the absence of the thousands of consultations referred to by experienced clinicians, it seems that roleplay with simulated patients, including structured feedback, is highly valued. Consistent with medical education literature supporting the use of experiential learning and simulated patients as providing safe opportunities to practice [24,25,27,43], students valued role-play with simulated patients over that with peers, but did cite a sense of pressure associated with being observed in group settings. Specific teaching approaches have been developed to manage small group environments [44] but medical faculty need to be supported and trained to deliver this teaching effectively.…”
Section: Discussionmentioning
confidence: 65%
“…The available evidence supports experiential learning models, with the use of actors as simulated patients, and opportunities for feedback and practice [25][26][27]. Multitudes of studies have shown short-term effects of such approaches on specific learning outcome measures.…”
mentioning
confidence: 86%
“…Informed Consent (IC, hereafter) is one of the aspects of professional practice that is generally and widely accepted in Western societies (Kihlbom 2008), although difficulties are still encountered in explaining it from a purely theoretical model (Alderson and Goodey 1998;Benbassat and Baumal 2009). Nevertheless, physicians are required by law and medical ethics to obtain informed consent from their patients before initiating treatment (Appelbaum 2007).…”
Section: Introductionmentioning
confidence: 99%